PERTANGGUNGJAWABAN TINDAKAN DISKRESI OLEH GUBERNUR DALAM PENYELENGGARAAN PEMERINTAHAN: Studi Kasus Kenaikan UMP di DKI Jakarta - Tegar Jati Pamungkas; Nur Anissa Meylani (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
This article discusses the form of the governor's authority in exercising discretion and how accountability for discretionary actions by the governor is in the context of the public interest. Discretion is a form of action carried out by the executive, judicial and legislative fields. The governor is a regional head with provincial status where he carries out the regional head's obligations in an autonomy as well as an administrative area. The governor as the regional head within the administrative area has the authority to carry out his functions in the legal system of state administration as the person in charge of the central government. The governor can carry out governmental legal actions because he is included in the organs of government, in this case regional government. This study uses a qualitative research method with a normative juridical approach. The subject in this study is the governor. Primary data sources in this study are laws and regulations, while secondary data sources in this study were obtained from journals, articles and news. This research resulted that the governor has an authority in carrying out discretionary actions as stipulated in the Government Administration Act which in its implementation must be in accordance with laws and regulations and the responsibility of the governor in carrying out these actions because according to the principle there is no authority without accountability. Where discretion can be null and void if it does not comply with the discretionary requirements, the continuation of discretion that does not meet the discretionary requirements results in social turmoil in the life of the state.